PENGARUH BEBAN LATIHAN DAN POWER LENGAN TERHADAP KETEPATAN PUKULAN SMASH PENUH BULUTANGKIS Studi Eksperimen Di PB. Remaja Semarang Tahun 2003 - Suratman, - (Universitas Negeri Semarang, 2009)
The research is aimed at finding out the different effect of maximumexercise load, sub maximum, the power of high and low arm and the interactionbetween exercise lead and arm power on the accuracy of badmintorn full smashstroke. The study was conducted at Remaja Badminton Club of Semarang in 2003.The number of the sample was 40 players. The design used was factorial 2x2. Theexercise load was measured with exercise load test which had validity coefficient onthe firs day 2.82 and on the second day 2.45. The reliablity coefficient was 0.99. Thearm power was measured with arm power test with validity coefficient on the first day238.09 and on the second day 245.92. The reliability coefficient was 0.996. Theaccuracy of the badminton full smash stroke was measured with badminton strokeaccuracy test with the validity coefficient on the first day 0.820 and the reliabilitycoefficient 0.937. The study showed that there was a different effect betweenmaximum exercise load and sub maximum (Fo = 184.02 > Ft = 4.11). There was adifferent effect between high arm power and low arm power (Fo =16.20 > Ft = 4.11).There was an interaction between exercise load and the arm power (Fo = 6,42>Ft =4,11) toward the accuracy of badminton full smash stroke.Kata kunci : beban latihan, power lengan, dan ketepatan pukulan smash penuhbulutangkis